City logistics challenges and innovative solutions in developed and developing economies: A systematic literature review. (17th August 2021) - Arvianto, Ary; Sopha, Bertha Maya; Asih, Anna Maria Sri; Imron, Muhammad Ali
Varying characteristics of developed and developing countries have resulted in different challenges and innovative solutions of city logistics. This study aimed to identify research clusters on city logistics between developed and developing economies and to systematically compare city logistics challenges and associated innovative solutions for both economies. Bibliometric analysis and a systematic literature review were applied to analyze 328 peer-reviewed publications, comprising 229 (70%) and 99 (30%) articles addressing case studies in developed and developing economies, respectively. We discovered six research clusters in city logistics literature for developed countries, compared with only four for developing economies in which public policy has not been addressed. Urban growth, environmental challenges, and traffic congestion are the three major city logistics challenges in both types of economies. Furthermore, fleet increment and inadequate loading/unloading spaces are the city logistics challenges analyzed in the literature on developing countries compared with the literature on developed economies that addresses the challenges of education deficiency, regulation, emergence of new business models, and network accessibility and capacity. Consequently, innovative solutions adopted by developed countries demonstrate varied processes involving technology, policy (including public policy and sustainability measures), infrastructure, and economic measures, while for developing countries, the focus remains on effective and efficient distribution operations using optimization and collaboration efforts.